Does TeamSTEPPS affect psychological status?. Issue 1 (11th February 2019) - Fukushima, Yoshinori; Yamada, Atsushi; Imoto, Naruaki; Iba, Toshiaki
Abstract : Purpose: The Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) program is known to improve team and clinical performance, but the relationship to psychological stress has not been clarified. The purpose of this paper is to evaluate team performance, clinical performance and psychological stress simultaneously in a simulation-based training combined with or without the TeamSTEPPS program. Design/methodology/approach: This randomized, controlled, prospective pilot study was performed to reveal TeamSTEPPS impact on psychological stress. The course included an emergency care training course, the TeamSTEPPS program, and a scenario simulation. Ten medical student teams were randomly allocated two groups: a TeamSTEPPS group and a non-TeamSTEPPS group. Team performance, clinical performance and psychological stress were evaluated simultaneously in the course; i.e., questionnaire evaluation and an observational evaluation for team performance; an assessor's evaluation and a simulator's evaluation for clinical performance. Autonomic nervous activity, represented by salivary amylase levels and heart rate variability, were measured as psychological stress indicators. Findings: Team performance and clinical performance were significantly better in the TeamSTEPPS group, while psychological stress did not differ between the groups. Originality/value: This is the first study to examine the relationship between TeamSTEPPS and psychological stress. Although only preliminary conclusions can be drawn from this small-scale study, results suggest that the TeamSTEPPS program improved team and clinical performance without increasing psychological stress.